Innovation, human capital and trade competitiveness : how are they connected and why do they matter? - Weresa, Marzenna A. (Cham : Springer, 2014)
'This work focuses on researching and establishing the importance of human capital and innovation as determinants of competitive advantages in international trade in the context of rapidly evolving technological advancement, globalization, and economic integration. The processes that accompany the shift from industrial economics to a knowledge-based economy are currently the object of interest of both scientists, politicians, investors and entrepreneurs. In many countries, the traditional sources of socioeconomic development, such as low labor costs, availability of inexpensive raw materials, and favorable geographic location are waning. These economies are searching for new sources of competitive advantage that will allow for maintaining growth, among other things by boosting participation in international trade ...' --Contratapa.
6. International Competitiveness of Countries with Performing Innovation Systems / Andreas Bielig, Jozef Olszynski, Grazyna Wojtkowska-Lodej, Oskar Kowalewski and Tomasz Napiorkowski ; 7. International Competitiveness of Countries with Catching-up Innovation Systems / Mariusz-Jan Radlo and Marcin Gomulka -- 8. International Competitiveness of Countries with Unbalanced Innovation Systems / Krzysztof Falkowski, Gunter Heiduk, Agnieszka McCaleb and Beata Michorowska -- Summary and Conclusions Regarding Economic Policies Supporting Medium and Long-Term Competitive Position of Domestic Goods on Foreign Markets -- Annexure: Sector Classifications.
Includes bibliographical references (p. 453-477)
Keywords: Development economics; Economic policy; Human capital; Regional economics